PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR POS BOYOLALI - Lamidi, Indriyatmoko, Amin Wahyudi & (Universitas Slamet Riyadi, 2016)
The results showed (1) style of leadership, not significant effect on the post office employee performance Boyolali, the first hypothesis is not proven true. (2) Motivation significant effect on the post office employee performance Boyolali. Thus the second hypothesis is accepted or proven true. (3) Discipline work not significant effect on the post office employee performance Boyolali, the third hypothesis is not proven true. (4) The effect of a significant style of leadership, motivation and discipline work together on employee performance in the Post Office Boyolali of Adjusted R2 value of 0,694 (69,4%) of the remaining 30,4% influenced by other variables outside the research model, meaning 4th hypothesis proved to be true. (5) The results of this study indicate that the determinants of employee performance Boyolali Post Office is work motivation, as well as the most dominant variables influence the employee's performance means that the hypothesis to 5 proved to be true. Keywords: leadership style, work motivation, labor discipline, employee performance.